SPECT and PET imaging of angiogenesis and arteriogenesis in pre-clinical models of myocardial ischemia and peripheral vascular disease - Hendrikx, Geert (Eur J Nucl Med Mol Imaging, 2016)
PURPOSE: The extent of neovascularization determines the clinical outcome of coronary artery disease and other occlusive cardiovascular disorders. Monitoring of neovascularization is therefore highly important. This review article will elaborately discuss preclinical studies aimed at validating new nuclear angiogenesis and arteriogenesis tracers. Additionally, we will briefly address possible obstacles that should be considered when designing an arteriogenesis radiotracer. METHODS: A structured medline search was the base of this review, which gives an overview on different radiopharmaceuticals that have been evaluated in preclinical models. RESULTS: Neovascularization is a collective term used to indicate different processes such as angiogenesis and arteriogenesis. However, while it is assumed that sensitive detection through nuclear imaging will facilitate translation of successful therapeutic interventions in preclinical models to the bedside, we still lack specific tracers for neovascularization imaging. Most nuclear imaging research to date has focused on angiogenesis, leaving nuclear arteriogenesis imaging largely overlooked. CONCLUSION: Although angiogenesis is the process which is best understood, there is no scarcity in theoretical targets for arteriogenesis imaging.